K KONSERVASI BAHAN PUSTAKA DI SEKOLAH DASAR NEGERI 1 BANJAR BALI: KONSERVASI - Made satria; I Made Pageh; Santana Sembiring (ACARYA PUSTAKA, 2026)
The objectives of this research are: (1) to identify the conservation activities carried out by the librarians at State Elementary School 1 Banjar Bali; (2) to determine the process of removing books from the shelves for conservation; and (3) to find out the constraints experienced during conservation activities at the Library of State Elementary School 1 Banjar Bali. This research uses a qualitative descriptive method, and the technique for selecting informants utilizes purposive sampling and snowball sampling. The author chose the Library of State Elementary School 1 Banjar Bali as the research location. In this study, the researcher used observation, interviews, and document study techniques to collect data in order to obtain concrete information. The results of the study show that: (1) The preservation of collections at the Library of State Elementary School 1 Banjar Bali includes four main pillars, namely active conservation (daily cleaning), passive conservation (monthly checking and room temperature control at 16°C), preventive conservation (the use of camphor and insecticides), and curative conservation (repairing slightly to moderately damaged books once a month); (2) The process of removing books begins with physical selection and classification based on the level of damage (minor, moderate, and severe). Severely damaged or destroyed books are separated from the shelves to be sent to the Education Agency for the asset writeoff process; (3) The constraints faced include a limited quantity of human resources that is disproportionate to the volume of the collection, as well as environmental factors such as high room humidity due to its location near a drainage ditch, a lack of sunlight exposure, and the use of wooden shelves that are susceptible to termite attacks.